Peningkatan Kemampuan Motorik Halus Anak Kelompok B Melalui Kegiatan Bermain Kreasi Loose Part.: Studi TK ABA 1 Pandean Karanganyar Ngawi - Puji Lestari; Agus Sriyanto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
This research was motivated by the low fine motor skills of group B children at TK Aisyiyah Pandean. This is because teachers are not optimal in choosing new learning methods, so that learning activities are less attractive and monotonous. Departing from this problem, the researchers used the loose part creation play method in order to improve the fine motor skills of the children of group B. The focus of this research is the application of the loose part playing method can improve the fine motor skills of group B children at TK Aisyiyah Pandean. The method in this study used Classroom Action Research (PTK) with the Kemmis & Taggart model. This research has several cycles, namely pre cycle, cycle I and cycle II. The data analysis technique in this study used descriptive qualitative and quantitative percentages. While the data collection technique of this research is observation, documentation, and interviews. The results of this study are: 1) The application of loose part play has succeeded in improving the fine motor skills of group B children at TK Aisyiyah Pandean. This can be proven in the selection of learning methods that take place and get a final score of 80, which is included in the very good criteria for assessment of 76-100. 2) There is an increase in each cycle, pre-cycle students have not developed (BB) as many as 1 child (6.7%), begin to develop (MB) as many as 9 children (60%), and develop according to expectations (BSH) as many as 5 children (33.3%), the first cycle of 15 children, 7 children or 47% of children got the start to develop (MB) and 8 children or 53% developed according to expectations, the second cycle, the scores of 15 children, 5 children or 47% children began to develop (MB), 7 children or 46.7% children developed according to expectations (BSH) and 3 children or 20% very well.